Compilers : principles, techniques, & tools \ - Aho, Alfred V. (New Delhi : Dorling Kindersly, 2007)
This introduction to compilers is the direct descendant of the well-known book by Aho and Ullman, Principles of Compiler Design. The authors present updated coverage of compilers based on research and techniques that have been developed in the field over the past few years. The book provides a thorough introduction to compiler design and covers topics such as context-free grammars, fine state machines, and syntax-directed translation.
This edition is manufactured in India and is authorized for sale only in india.
includes index.
Keywords: Compilers (Computer programs).